A novel methodology for assessing, evaluating, and classifying defects in clear aligner attachments - Nash Linton J.; Blundell Haylea L.; Weir Tony (Australasian Orthodontic Journal, 2025)
Attachments are composite resin geometries considered important adjuncts for clear aligner therapy (CAT)effectiveness. They are bonded to the tooth surfaces to improve control during orthodontic tooth movement (OTM). Attachments augment tooth surfaces to facilitate force application to achieve the desired OTM and also to enhance the retention of the aligner. A comprehensive description of CAT attachment morphology, commonattachment defects, or a scientific methodology to assess attachment clinical placement and dimensions has not been described. This paper discusses morphologic and geometric features (active surface, passive surface, base, and ridges) of attachments and introduces a classification system for attachment defects (volumetric, abrasion, location, and errors). Finally, a systematic methodology to assess attachment defects is outlined to allow for further research into attachment placement in a clinical setting.